An Analysis of Interrogative Sentences in the Film Little Monsters 2019 By Abe Forsythe - Febry Sarah A. Tampubolon; Carolin Oktavia Sitompul; Resperdiana Purba (Jurnal Ilmiah Wahana Pendidikan, 2021)
The title of this study is "An Analysis of Interrogative Sentences in the Film Little Monsters 2019 by Abe Forsythe". The study identified and analyzed the types of interrogative sentences and what types of sentences were used the most in the film. Researchers use qualitative descriptive research methods by using analysis documents to obtain the desired results. Researchers collected 108 question sentence data. The results showed that, first, the types of question sentences contained in the film Little Monsters 2019 are the question tag, yes-no question, and w-h question. The type of question tag as much as 1 data, the yes-no question sentence as much as 41 data after summing up from the use that uses auxiliary verb with those that without an auxiliary verb, and question sentence w-h question as much as 66 data including from the word what, who, where, when, why, and how. Second, the data analyzed showed that the question sentence with the most frequency of use was the w-h question, while the least frequency of use was the question tags. Keywords : interrogative sentence, little monsters, tag question, w-h question, yes-no question